2021
DOI: 10.1371/journal.pntd.0009393
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide resistance status and mechanisms in Aedes aegypti populations from Senegal

Abstract: Aedes aegypti is the main epidemic vector of arboviruses in Africa. In Senegal, control activities are mainly limited to mitigation of epidemics, with limited information available for Ae. aegypti populations. A better understanding of the current Ae. aegypti susceptibility status to various insecticides and relevant resistance mechanisms involved is needed for the implementation of effective vector control strategies. The present study focuses on the detection of insecticide resistance and reveals the related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 52 publications
2
54
0
3
Order By: Relevance
“…Several genes of the family cytochrome P450 and glutathione-S-transferases (GSTes) have been associated with pyrethroid and DDT resistance in Ae . aegypti populations [ 35 , 67 , 68 ]. For instance, a study by Helvecio et al [ 69 ] found that several SNPs in GSTe2 correlated with temephos resistance in Ae .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several genes of the family cytochrome P450 and glutathione-S-transferases (GSTes) have been associated with pyrethroid and DDT resistance in Ae . aegypti populations [ 35 , 67 , 68 ]. For instance, a study by Helvecio et al [ 69 ] found that several SNPs in GSTe2 correlated with temephos resistance in Ae .…”
Section: Discussionmentioning
confidence: 99%
“…aegypti resistance to DDT and presence of GSTe2 SNPs observed (L111S, C115F, P117S, E132A, I150V, E178A, and A198E). In Senegal, Sene et al [ 68 ] also reported higher phenotypic resistance to DDT and permethrin in Ae . aegypti but, similar to this study, no kdr mutations were detected.…”
Section: Discussionmentioning
confidence: 99%
“…Each extraction pool was comprised of up to 30 mosquitoes of the same species, collected from the same or neighbouring municipalities and from the same collection date. The concentration and purity of the extracted (pooled) RNA was determined by spectrophotometry using a NanoDrop 2000c spectrophotometer (Thermo Fisher Scientific, Waltham, MA, US) and its integrity was confirmed via 1% w/v agarose gel electrophoresis as previously described [ 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…albopictus and Cx . pipiens pools, based on the method described by [ 49 ] ( S1 and S2 Tables) . WNV-specific detection analysis was performed in all pools (regardless of the respective Pan-Flavivirus assay outcome) with a multiplex Real Time one step RT-PCR TaqMan assay that simultaneously detects and differentiates WNV-lineage 1 from WNV-lineage 2 [ 55 ].…”
Section: Methodsmentioning
confidence: 99%
“…The susceptibility status of the targeted vector populations to the used insecticides were generally not studied [ 81 ]. Insecticides susceptibly tests should be always done before insecticide spraying operations [ 82 ]. To the best of our knowledge, larviciding using abate and larvivorous fishes to control dengue vectors were only used in Cabo Verde.…”
Section: Vector Controlmentioning
confidence: 99%